Developing scientific competencies: a collaboration between High School teachers and Physics researchers to create experiment-based learning activities. Issue 1 (May 2021) - Pallotta, Filippo; Parola, Alberto; Bondani, Maria
Abstract: The last EU recommendations on key competences for lifelong learning encourage educational institutions to strengthen the collaboration between Physics researchers and Secondary School teachers to implement competence-oriented education, training and learning. Our group has carried out a collaboration project with a group of high school physics teachers engaged in a PLS (Progetto Lauree Scientifiche) professional development course promoted by the Department of Science and High Technology (DiSAT – Dipartimento Scienze e Alta Tecnologia) of Insubria University in Como, Italy. The aim of the course was to enable teachers to create balanced and effective learning activities to be used in class to reinforce the scientific competencies and skills required in the Final Exam of the Italian Secondary School (Esame di Stato) and in the entire physics curriculum. This paper presents the result of this collaboration to understand how to better support the collaboration between Physics researchers and High School teachers in order to design teaching and learning materials that can be effectively integrated in the daily classroom activities, focusing the attention on problem solving and data interpretation skills, as requested by the last education reform for Italian Secondary School Final Exam.